Creative Flows: Constructions of Meaning Between Binary Oppositions, Paradoxes and Common Sense - D’Alessandro, Simone (Italian Sociological Review, 2023)
Is it possible to construct a stable discursive field of the term ‘creativity’? Does the construction of its meaning follow a conventional route, as with other words, or does it constitute an exception? Do creativity professionals construct meanings close to or far from common sense? What are the relationships between the term creativity and the terms freedom, constraint, routine, and innovation Starting from the above questions, this empirical research examines the construction of meaning of the term ‘creativity’ in an attempt to capture aspects “that people tend to share and take for granted, generating both recurrent patterns and variations” (Spillman, 2022, p. 24). By analysing interviews with 27 professionals working in creative and/or innovative fields, the research identifies stereotypes, rituals, binary oppositions, and paradoxical expressions present in the discursive fields of the interviewees. While scholars of the subject classify the term ‘creativity’ by means of stable and consistent definitions, professionals actually working in the creative fields come up with ambiguous, contradictory, and paradoxical definitions. With a few exceptions, the definitions recorded during the interviews are similar to common sense phrases found in the collective imagination. Creative practitioners use the same repertoires and discursive fields as everyone else and augment the rhetorical narrative of the term. Paradoxes, oscillations between polarities and ambiguous definitions given by professionals working in the creative fields show “the emerging properties that relate symbols, phenomena, contexts and people” (Donati, 2022, p. 317).